E-Commerce Berbasis Web Pada BUMDes Arto Moro Tukinggedong Kabupaten Kebumen Menggunakan Metode Agile - Rizki Wahyudi; Purwanto, Purwanto; Luthfi Nur Azizah (Journal Of Informatics And Busisnes, 2025)
BUMDes Arto Moro in Tukinggedong Village still faces challenges in managing sales, recording transactions, and monitoring inventory, which are currently performed manually. This study aims to design and implement a web-based e-commerce system using the Agile method to support digitalization of sales management and product marketing more efficiently and transparently. The research employed a qualitative approach with data collected through observation, interviews, documentation, and questionnaires distributed to system users. The black-box testing results indicate that all system features functioned according to requirements. Furthermore, questionnaire results show that administrators rated the system 94% (very good), indicating operational effectiveness, while customers rated 92% (very good), showing usability and satisfaction. This confirms that the developed system effectively replaces manual methods, simplifies transactions, and accelerates inventory management for BUMDes.